2021
DOI: 10.3390/md19080409
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Viral Applications of Marine Resources for COVID-19 Treatment: An Overview

Abstract: The ongoing pandemic has led to an urgent need for novel drug discovery and potential therapeutics for Sars-CoV-2 infected patients. Although Remdesivir and the anti-inflammatory agent dexamethasone are currently on the market for treatment, Remdesivir lacks full efficacy and thus, more drugs are needed. This review was conducted through literature search of PubMed, MDPI, Google Scholar and Scopus. Upon review of existing literature, it is evident that marine organisms harbor numerous active metabolites with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
(209 reference statements)
0
20
0
Order By: Relevance
“…The presence of halogenated compounds in these demosponges has been suggested to play a protective role against diverse microorganisms [15,31]. Recently, it was shown that such brominated compounds as bromotyrosines are localized within so-called spherulocytes, highly specialized cells which are responsible for the biosynthesis of these very effective antivirals [43], antibacterial [31], and cytotoxic [44,45] compounds. These cells have been reported within the outermost layers of corresponding skeletal fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of halogenated compounds in these demosponges has been suggested to play a protective role against diverse microorganisms [15,31]. Recently, it was shown that such brominated compounds as bromotyrosines are localized within so-called spherulocytes, highly specialized cells which are responsible for the biosynthesis of these very effective antivirals [43], antibacterial [31], and cytotoxic [44,45] compounds. These cells have been reported within the outermost layers of corresponding skeletal fibers.…”
Section: Discussionmentioning
confidence: 99%
“…that such brominated compounds as bromotyrosines are localized within so-called ulocytes, highly specialized cells which are responsible for the biosynthesis of the effective antivirals [43], antibacterial [31], and cytotoxic [44,45] compounds. The have been reported within the outermost layers of corresponding skeletal fibers the localization of Br and Ca in the same layers has been shown by us using CµX cannot yet speculate about the possible role of brominated compounds in calcifica contrast, the templating activity of chitin with respect to the formation of calci bonate-based biominerals is well recognized [3,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Seafood and its products are essential because of the richness of their essential micronutrients, including several vitamins, dietary proteins as well as omega-3 fatty acids, principally long-chain ω-3 polyunsaturated fatty acids (LC n-3 PUFA), such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), which are beneficial for humans ( Inanli et al, 2020 ). In addition, antiviral compounds from marine resources have been evaluated and found helpful in COVID-19 treatment ( Zahran et al, 2020 ; Geahchan et al, 2021 ). However, seafood quality can be decreased due to enzymatic, chemical, and microbiological deterioration, which can cause several safety issues ( Inanli et al, 2020 ).…”
Section: The Effect Of Covid-19 On Processing Methods For Seafoodmentioning
confidence: 99%
“…This supremacy also comes with their various biological activities and chemical diversity. Herein, cytotoxicity or its related anti-cancer properties is the leading interest for these biological activities (Hanif et al 2019 ), followed by antibacterial and other distinct properties, ranging from antiviral properties that serve as potential leads for COVID-19 therapy (Geahchan et al 2021 ), enzyme inhibitors for pharmacological application (Ruocco et al 2017 ; Yamazaki et al 2020 ) to lead compounds for type II diabetes treatment (Abdjul et al 2017 ), including potential anti-inflammatory agents involved in various diseases such as heart disease, lung disease, bone health, depression, cancer, and anger and aggressive disorders (Kumar and Patravale 2020 ). Thus, the Indonesian marine sponges are an excellent source of bioactive compounds, especially with cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%